The Impact of COVID 19 on Foreign Investors : Evidence from the Quarterly Global Multinational Enterprise Pulse Survey for the First Quarter of 2021 - Saurav, Abhishek; Kusek, Peter; Kuo, Ryan; Viney, Brody (World Bank, Washington, DC, 2021)
As the Coronavirus (COVID-19) pandemic enters its second year, foreign investors can see light at the end of the tunnel as economic conditions improve. Results from the latest round (Q1 2021) of World Bank Group’s quarterly pulse surveys of Multinational Enterprise (MNE) affiliates suggests that most firms are still operating below full capacity. The pandemic’s adverse effects on MNEs in developing countries continued to ease in the first quarter of 2021 (Q1 2021). Impacts remained widespread with 93 percent experiencing at least one adverse impact, but fewer firms report negative demand, output, revenue, and profit impacts (relative to Q1 2020) than in prior survey rounds. The average magnitude of these impacts was also more limited and continued to ease from Q4 2020. The longer-term outlook for foreign investment in developing countries remains subdued. Overall, 92 percent of firms report that their foreign parent had no plans to change (increase or decrease) the company’s level of investment over the next 1-3 years. Uncertainty about future demand is the key factor holding investment back, but policy and regulatory restrictions are also a factor for almost half of firms. Survey results confirmed that almost all MNE affiliates have increased their adoption of digital technologies for remote working, e-commerce, and supply chain management in response to the pandemic. Half of MNE affiliates also report increasing their focus on sustainability and decarbonization of products and services, with foreign parent companies again playing a critical role. While these survey results may not be generalizable to all developing countries, they are directionally indicative of MNEs’ experiences in developing countries